CAPITAL MARKET REACTIONS TO THE ANNOUNCEMENT OF STOCK SPLIT (STUDIES ON GO PUBLIC COMPANI THAT PERFORM A STOCK SPLIT YEARS 2011-2015 IN THE INDONESIA STOCK EXCHANGE) - Langelo, Juandy Seiver (Manajemen Bisnis, 2016)
The purposes of this research is to investigate the market?s  reaction events of the stock split announcement, proxied by abnormal returns and trading volumes. Hypothetical test in this research was using paired sample t test in the differences of abnormal return and wilcoxon signed rank to trading volume.Based on the results of hypothetical test, this research concluded that the market reacts negatively against the event of stock splits. The conclusion obtained from the presence of significant decrease of average volume of trade after the split event, where as the average of abnormal return decreases however not significant after the event of stock splits.